2021
DOI: 10.1038/s41388-020-01638-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypoxic long noncoding RNA KB-1980E6.3 maintains breast cancer stem cell stemness via interacting with IGF2BP1 to facilitate c-Myc mRNA stability

Abstract: The hostile hypoxic microenvironment takes primary responsibility for the rapid expansion of breast cancer tumors. However, the underlying mechanism is not fully understood. Here, using RNA sequencing (RNA-seq) analysis, we identified a hypoxia-induced long noncoding RNA (lncRNA) KB-1980E6.3, which is aberrantly upregulated in clinical breast cancer tissues and closely correlated with poor prognosis of breast cancer patients. The enhanced lncRNA KB-1980E6.3 facilitates breast cancer stem cells (BCSCs) self-ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 69 publications
2
103
0
Order By: Relevance
“…Indeed, RNF144A-AS1 could cooperate with EIF2AK2 to inhibit the expression of IFN-γ revealed by Huynh et al [ 36 ]. Similarly, in GC, RNF144A-AS1 may interact with RNA-binding protein to influence gene expression or act as a cofactor for transcriptional factors and chromatin modifiers to participate in gene regulation, considering the portion of nuclear localization of it [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, RNF144A-AS1 could cooperate with EIF2AK2 to inhibit the expression of IFN-γ revealed by Huynh et al [ 36 ]. Similarly, in GC, RNF144A-AS1 may interact with RNA-binding protein to influence gene expression or act as a cofactor for transcriptional factors and chromatin modifiers to participate in gene regulation, considering the portion of nuclear localization of it [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LINC00958 regulated by m6a modification can promote breast cancer tumorigenesis through miR-378a-3p and YY1 axis ( Rong et al, 2021 ). A novel hypoxic long-stranded noncoding RNA KB-1980E6.3 maintains stemness in breast cancer stem cells by interacting with IGF2BP1 to promote the stability of c-Myc mRNA ( Zhu et al, 2021 ). MALAT1 promotes thyroid cancer progression by binding to miR-204 and upregulating IGF2BP2, thereby affecting miR-204/IGF2BP2/m6A-MYC signaling ( Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that m6A modification can stabilize and promote the expression of MYC through the IGF2BP pathway [5,49,76], or by stabilizing AFF4, maintaining the transcription of MYC and affecting cell proliferation [77]. Interestingly, lncRNA KB-1980E6.3 can bind to the recognition protein IGF2BP1 to synergistically stabilize c-Myc mRNA [78]. In addition to MYC, the well-known tumor suppressor gene PTEN is also regulated by m6A modification.…”
Section: N6-methyladenosine Can Be Associated With Cancer Cell Proliferationmentioning
confidence: 99%